Microvascular density assessed by CD31 predicts clinical benefit upon bevacizumab treatment in metastatic colorectal cancer: results of the PassionATE study, a translational prospective Phase II study of capecitabine and irinotecan plus bevacizumab followed by capecitabine and oxaliplatin plus bevacizumab or the reverse sequence in patients in mCRC. (August 2020) - Bianconi, Daniela; Herac, Merima; Posch, Florian; Schmeidl, Margit; Unseld, Matthias; Kieler, Markus; Brettner, Robert; Müllauer, Leonhard; Riedl, Jakob; Gerger, Armin; Scheithauer, Werner; Prager, Gerald
Background: Targeted therapies offer novel opportunities to explore biomarkers based on their mode of action. Taking this into consideration, we evaluated six angiogenesis-related proteins as potential predictive biomarkers, which expression might predict the benefit of bevacizumab treatment in patients with metastatic colorectal cancer (mCRC). Methods: This was a phase II multicenter, two-armed, randomized study, in which patients with mCRC were treated with XELIRI (capecitabine and irinotecan) plus bevacizumab followed by XELOX (capecitabine and oxaliplatin) plus bevacizumab (Arm A) or the reverse sequence (Arm B). Tissue expression level of six prespecified candidates [microvessel density assessed by CD31, PTEN, αV integrin, CD98hc, uPAR and NRP-1] was analyzed via immunohistochemistry. The prognostic impact on survival was quantified using the Cox regression model. The predictive potential for benefit from Arm A versus Arm B treatment was investigated by fitting an interaction between the biomarkers and treatment assignment within a multivariable Cox model. Results: In total, 74 out of 126 patients were included in the analysis. The expression of PTEN, αV integrin, uPAR and NRP-1 was not associated with progression-free survival (PFS) or overall survival (OS). For the first time, we identified that patients with tumors expressing CD98hc had a longer PFS than patients without CD98hc-expression ( p  = 0.032). More importantly, and in accordance with previous studies, low microvessel density was found to be associated with a reduced PFS [adjusted HR per doubling of CD31-expression ( p  = 0.53, 95% confidence interval: 0.30–0.95, p  = 0.034)]. Conclusions: These results can contribute to the development of a personalized strategy for the treatment of mCRC with bevacizumab.